ANALISIS PENGARUH VARIASI MENU MAKANAN TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN BANDAR DJKARTA, ALAM SUTERA - Velicia Sumantri; Roles Ni Made Sri Puspadewi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The purpose of this research is to see whether variations in the food menu have an impact on purchasing decisions at restaurants in Bandar Djakarta Alam Sutera. The research was carried out using quantitative descriptive research methods. Data were obtained from the results of distributing questionnaires to 100 respondents. The questionnaire consists of 35 statements using a Likert scale online using the Google form. The results of the questionnaires distributed were then processed using the SPSS tool with regression analysis. Based on the analysis conducted, it was found that most of the respondents in this study were female, aged 17 to 21 years. From the validity and reliability tests performed, the results show that the data is valid and reliable. The findings of this study also meet the classical assumption requirements. In the linear regression analysis, it was found that the variation in the food menu had an influence on the purchase decision with a constant value of 0.874 and based on the results of the determination coefficient carried out, it was known that the impact of the food menu variation on the purchase decision was 52.6% while the rest was driven by other things outside this research. From the results presented, it can be concluded that variations in the food menu can influence purchasing decisions.